2010
DOI: 10.1590/s0100-40422010000500016
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of native wood charcoal by infrared spectroscopy

Abstract: Recebido em 24/8/09; aceito em 7/1/10; publicado na web em 23/4/10 Brazil is one of the largest producers and consumers of charcoal in the world. About 50% of its charcoal comes from native forests, with a large part coming from unsustainable operations. The anatomic identification of charcoal is subjective; an instrumental technique would facilitate the monitoring of forests. This study aimed to verify the feasibility of using medium and near infrared reflectance spectroscopy to discriminate native (ipê) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…In wood (Figure 2a), bands at 8749cm -1 and 8547 cm -1 are related to aromatics of lignin; bands at 6800 cm -1 and 4401 cm -1 are attributed to hemicelluloses; regions near 6110-5697 cm -1 and 4335-4146 cm -1 are related to all cell wall components; the peak at 5200 cm -1 is from water, while that at 5995 cm -1 is related to extractives content (Tsuchikawa and Siesler 2003, Yonenobu and Tsuchikawa 2003, Schwaninger et al 2011. In charcoal, small absorption was verified (Davrieux et al 2010 and some irregularities in spectra were influenced by water OH bands (region near 7073-7181 and 5142 cm -1 ) and degradation of cell wall components (4335-4146 cm -1 ).…”
Section: Nir Characteristics Of Wood and Charcoalmentioning
confidence: 97%
See 1 more Smart Citation
“…In wood (Figure 2a), bands at 8749cm -1 and 8547 cm -1 are related to aromatics of lignin; bands at 6800 cm -1 and 4401 cm -1 are attributed to hemicelluloses; regions near 6110-5697 cm -1 and 4335-4146 cm -1 are related to all cell wall components; the peak at 5200 cm -1 is from water, while that at 5995 cm -1 is related to extractives content (Tsuchikawa and Siesler 2003, Yonenobu and Tsuchikawa 2003, Schwaninger et al 2011. In charcoal, small absorption was verified (Davrieux et al 2010 and some irregularities in spectra were influenced by water OH bands (region near 7073-7181 and 5142 cm -1 ) and degradation of cell wall components (4335-4146 cm -1 ).…”
Section: Nir Characteristics Of Wood and Charcoalmentioning
confidence: 97%
“…For carbonized material, near infrared spectrometry has been used to distinguish species (Davrieux et al 2010, Nisgoski et al 2015b) and carbonization processes (Monteiro et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al [41] commented that chemical and physical characteristics of wood components in cell walls can be easily changed by increasing carbonization temperature. Also, Davrieux et al [12] separated charcoal samples of Tabebuia serratifolia from Eucalyptus grandis by applying PCA and discriminant factorial analysis with NIR spectra in raw form. Evaluating all samples, species and carbonization process ( Fig.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…Also, application of near infrared spectroscopy (NIR) has been evaluated. Studies indicate the possibility of distinguishing carbonized material from native and planted forests [12,13], some carbonization characteristics [14,15] and also species discrimination [16][17][18]. Final results must be compared, and so, a database is necessary in species distinction by anatomy and spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…OLIVEIRA et al (2015), analysing the spectra of timber of four species of trees showed able to separate this species by NIR spectroscopy and Artificial Neural Networks. In another way, for native wood charcoal, near infrared spectrometry has been used to distinguish species (DAVRIEUX et al, 2010;NISGOSKI et al, 2015). Another study combined visible and near-infrared spectroscopy to discriminate solid wood samples of two Corymbia spp.…”
Section: Introductionmentioning
confidence: 99%